DESIGNING STORYTELLING INSTRUCTION FOR SENIOR HIGH SCHOOL SPEAKING - Biuti Badarul Alam Nimas Puspita Arruum; Wardah Wardah; Yuniarti Yuniarti (PENA KREATIF : JURNAL PENDIDIKAN, 2022)
This research aimed at designing and developing the procedure of storytelling technique activities in teaching speaking narrative text. This research was conducted at SMA Negeri 1 Ambawang in the academic year 2020/2021. This research was development research which consists of three phases; analysis, design, and development. The result of the analysis in this research showed that the students lack vocabulary and have little time to get a chance to speak English. The result of this research was an instructional design of storytelling. The result of designing storytelling instruction is formed in a lesson plan of teaching speaking narrative text. The designed storytelling instruction consists of six sections: introduction, observing, guiding, practicing, assessing, and closing. It is recommended that the teacher use storytelling techniques to teach English especially in speaking skill